Superior mesenteric artery syndrome masquerading as chronic gastric volvulus in a child with severe acute malnutrition: a case report - Ali, M. Mokarram; Kumar, Amit; ., Rashi; Sinha, Amit K.; Kumar, Bindey (International Surgery Journal, 2020)
Superior mesenteric artery (SMA) syndrome is a rare cause of high intestinal obstruction. It is commonly seen in severely malnourished patients presenting with repeated episodes of vomiting. We report a case of SMA syndrome in a 3 years old male child provisionally diagnosed as chronic gastric volvulus with severe acute malnutrition. The diagnosis of SMA syndrome was confirmed on abdominal exploration. SMA syndrome is a rare case of intestinal obstruction in paediatric age group. Chronic malnutrition is one of the common causes of this entity. There should be a high index of suspicion for this syndrome when we encounter a child with severe malnutrition and recurrent vomiting.